KOMISI PENYIARAN INDONESIA SEBAGAI STATE AUXIALIARY BODIES YANG MENJAMIN SIARAN YANG LAYAK BAGI ANAK - Arliman S, Laurensius (Veritas et Justitia, 2017)
This article discusses a number of questions, i.e. regarding the role and function of the Indonesian Broadcasting Commission, established by Law no. 32 of 2002, as a state auxiliary body, in supervising Indonesian broadcasters; 2. The Commission’s role in guaranteeing the broadcast of material that are suitable for children; and 3. Offering inputs as to how to secure child-proof broadcasts. The Commission already issued a number of regulations in that respect but practice shows low compliance. Parents and adults should be more involved, pay more attention and offer guidance to children.